ASSESSMENT OF PROGNOSTIC FACTORS CONSIDERING THE VOLUME OF SKELETAL METASTASIS IN PATIENTS WITH DISSEMINATED PROSTATE CANCER - N. E. Kosyh; A. V. Eremenko; S. Z. Savin (Сибирский онкологический журнал, 2017)
Purpose. To determine the correlation between prognostic factors (age, differentiation grade assessed using the Gleason scoring system, serum prostate specific antigen, prostate volume, and serum testosterone) and the volume of skeletal metastasis expressed as bone metastasis index (BMI) in patients with disseminated prostate cancer (DPC). Material and methods. We conducted a retrospective analysis of 157 patients with initially diagnosed DPC treated at the Khabarovsk Regional Cancer Center from 2003 to 2013. Bone metastases were revealed in all patients. The volume of skeletal metastasis was measured using a novel automated computeraided diagnosis system devised by the specialists of Computer Center of the Russian Academy of Sciences. Results. The patients were divided into four groups. Group1: BMI≤1 % and Gleason score≤5; group 2: BMI ≤1 % and Gleason Score≥3; group 3: BMI>1 % and Gleason score≤5; group 4: BMI>1 % and Gleason score>5. The median survival time was 48 months in group 1 patients, 36.5 months in group 2, 33 months in group 3 and 20 months in group 4 patients. Both log-rank and Wilcoxon tests demonstrated a statistically significant difference in survival curves between the groups 1 and 3, and between the groups 2 and 4. There was also a difference in differentiation grade assessed by the Gleason score system between these two pairs of groups. Correlation of other prognostic factors, such as age, serum prostate specific antigen, prostate volume, and serum testosterone with the volume of skeletal metastasis demonstrated that BMI predominantly influenced the survival of prostate cancer patients. Conclusion. The assessment of prognostic factors allowed the patients’ groups with the worst prognosis to be identified. The bone metastasis index and differentiation grade of the tumor appeared to be independent predictors of high death risk in patients with disseminated prostate cancer.